(untitled) (Research, Society and Development, 2021)
Heart Failure is the failure of the cardiovascular system to supply the metabolic needs of the body tissues. Such condition is aggravated by endothelial dysfunction, in which there is an imbalance in the endothelial production of mediators that regulate vascular homeostasis. Thus, the objective of this study was to review the literature about the influence of physical activity on endothelial function and in the induction of endothelial progenitors in individuals with HF. Integrative review of literature in the PubMed database of productions from the last 10 years. The descriptors used were: "Heart Failure", "Exercises", "Physical Activity", and "Endothelial Progenitor Cells", which were combined to delimit the search. Nine articles were selected at the end of the search steps. Being the year 2010 the most prevalent with 33.3% of publications, followed by the year 2013 with 22.2% of publications. Regarding the country of origin of the studies, 66.6% were conducted in Germany, Belgium, and Taiwan (22.2% in each of the cited countries), followed by studies conducted in Italy, Greece, and the United Kingdom, each country with 11.1%. Evidence was found showing the effectiveness of exercise on endothelial repair and vascular mediator production, with emphasis on endothelial progenitor cells (EPCs). In patients with heart failure of varying degrees, an increase in muscle neovascularization and an improvement in cardiac function are observed after physical activity, induced by EPCs. Thus, together with drug therapies, the adoption of lifestyle changes and physical exercise in individuals with heart failure and endothelial dysfunctions are recommended. Evidence also shows that there is an increase in the mobilization of other mediators that contribute to such improvements, such as CD34+ and VEGF. Regarding the improvement of endothelial function and the induction of endothelial progenitors, on average, the studies analyzed showed satisfactory results that clarify the importance of physical exercise in the quality of life and survival of HF patients.